Determination of Heavy Metal Pollution in the Dankran River in the Bekwai Municipality of Ghana - Vivian Afriyie; Lyndon N. A. Sackey; Linda Aurelia Ofori (Journal of Chemistry)
Water pollution has been a major issue across the globe because of industrial activities to meet the needs of people. Many chemicals are released into the environment through these processes, which affect human health and the environment. Hence, the study aimed to assess the concentration of heavy metals (Cu, Zn, Mn, Ni, Hg, and Fe) and the physicochemical and biological properties of the Dankra River. The samples were taken from three locations, Konyaw, Jumako, and Anwiankwanta, and subjected to standard laboratory tests using Atomic Absorption Spectroscopy (AAS) and Inductively Coupled Plasma Mass Spectroscopy (ICP-MS). Results revealed that the Dankran river was not polluted with the selected heavy metals under study. The physicochemical properties, the biological oxygen demand (BOD), chemical oxygen demand (COD), and nitrogen, phosphorus, and potassium (NPK) concentrations were all within the allowable healthy limits according to WHO standards. Iron was the predominant metal in the Dankran river, with the highest concentration of 6.5913 mg/l. Thus, the river is safe to use, but there is a need for regular monitoring to support life. The order of concentration of the investigated metals follows this pattern in descending order: Fe > Mn > Cu > Zn > Ni > Hg.